- Pengaruh Bank Indonesia Rates dan Federal Fund Rates terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia - Abdul Manap; Rini Yulia Sasmiyati; Norman Edy; Mustangin Mustangin; Mohamad Ramadhan Agung Nugroho (Al-Buhuts, 2023)
The purpose of this study was to determine the effect of Bank Indonesia Rates (BI Rates) and Federal Fund Rates. This study used secondary data, especially data from Bank Indonesia and The Federal Reserve. This data is time series data (monthly) from December 2020 to December 2022. Data analysis used multiple regression because there were two or more independent variables. In this classic assumption or regression assumption test, there are four assumption tests that must be fulfilled in the regression analysis, namely the Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test. In testing, Bank Indonesia Rates and Federal Fund Rates have significant and simultaneous effect on the IDX Composite. The coefficient of determination of R Square was 0.589 or around 58.9%. It can be concluded that these figures indicate that the BI Rates and Federal Fund Rates have a contribution in explaining the variation of the IDX Composite variable of 58.9% while the remaining 41.1% is influenced by other variables, this illustrates the implementation of monetary policy which is still expansive.